Conservative revolutionary : the lives of Lewis Namier - Hayton, David, 1949-; Manchester University Press (Manchester, UK : Manchester University Press, 2019)
Acclaimed after the Second World War as England's greatest historian, Sir Lewis Namier was an eastern European immigrant who came to idealise the English gentleman and enjoyed close friendship with leading figures of his day, including Winston Churchill. Today, Namier is associated with the belief that the thoughts and actions of elites matter most, and with a view of politics in which those who enter public life do so only in pursuit of personal and material advantage. This exaggerated view has made him a hero to social and political conservatives, and a demonic figure to the Left. Preoccupied by nationalism, empire, and human motivation, Namier also remains famous in academic circles for supposedly declaring that any reference to ideas in political discourse was nothing more than 'flapdoodle'. The first biography of Namier in over thirty years, this book is based on a vast range of sources, including rich new archival material.
Prologue: In search of Namier -- 1. Avenues of history: the child and the man, 1888-1913 -- 2. Personalities and powers, 1913-1917 -- 3. Facing east, 1917-1920 -- 4. In the margin of history,1920-1928 -- 5. Skyscrapers, 1928-32 -- 6. Europe in decay, 1932-8 -- 7. In the Nazi era, 1938-47 -- 8. Crossroads of power, 1947-56 -- 9. Conflicts, 1956-60 -- 10. Vanished supremacies: Namier in retrospect -- Index.
Includes bibliographical references and index.
In English.
Description based on print record.
Available through ManchesterHive.
JSTOR
Keywords: Namier, L. B. -- 1888-1960.; Namier, L. B. -- 1888-1960; Namier, Lewis, -- 1888-1960.; Namier, Lewis; Historians -- Great Britain -- Biographies; HISTORY / Historiography; Historians; Great Britain; Historiens -- Grande-Bretagne -- 20e siecle; Biographies